Assessment Of Quality Of Healthcare And Patients' Satisfaction In Iranian Hospitals, A TRM Approach - Farzan, Farzaneh (2009)
The purpose of the study is to examine and develop a better understanding of the relationship between service quality and patient satisfaction level. To examine the major factors affecting patients' perception of cumulative satisfaction and to address the question whether patients in Iran evaluate quality of health care similarly or differently.